Photosensitizing Activity of Nanoparticles of Poly (2-amino phenol)/Gold for Intensified Doxorubicin Therapeutic Effect on Melanoma Cancer Cells under Synergism Effect of 808-nm Light - Naghmeh Sattarahmady; Zahra Kayani; Hossein Heli; Parsa Faghani-Eskandarkolaei; Hanieh Haghighi (Journal of Biomedical Physics and Engineering)
Background: Photothermal therapy (PTT) is one of the effective and non-invasive strategies which hold great promise for improving the treatment of cancer cells. PTT is based on activating a photosensitizer by infrared light irradiation and producing heat and reactive species and apoptosis in the tumor area.Objective: The aim of this study was to investigate the effect of photothermal/chemotherapy on melanoma cancer cells using poly (2-amino phenol)/gold (P2AO/AuNPs) and doxorubicin (DOX).Material and Methods: In this experimental study, nanoparticles of P2AO/AuNPs were synthesized, and their mixture with DOX was applied as a photosensitizer for photothermal/chemotherapy of a C540 (B16-F10) melanoma cell line.Results: P2AO/AuNPs generated heat and cytotoxic responsive oxygen species (ROS) upon 808-nm light irradiation with simultaneous intensifying DOX therapeutic effect under domination of synergism effects between light irradiation, P2AO/AuNPs, and doxorubicin. Cell treatment with both P2AO/AuNPs and DOX resulted in a considerable increase in necroptotic cells to 61% with a significant decrease in the living cells (39%).  Conclusion: P2AO/AuNPs provided a platform for light absorption and intensifying DOX therapeutic effect. This study approved the applicability of a new photothermal/chemotherapy by domination of synergistic effects attained by combination of laser light, P2AO, AuNPs, and DOX.